DEVELOPMENT OF THE STATE SUPPORT FORMS PROJECTS IN INDUSTRIAL BUILDING - I. M. Meilanov; A. M. Esetova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Aim. The topicality of the research is stipulated by the objective necessity of the organizational and economic mechanism improvement of the state support projects of the industrial building. The aim of the research is the development of conceptual provisions and methodological foundations of financial projects creating conditions for economic growth of Russia based on the construction and putting into effect industrial objects.Methods. In the course of the research the system, subject-functional and structural approaches were implemented to solve the problems set widening the scope of the complex approach to assessment of the current operating mechanism of the state financial support of the projects and financial volume; to criteria stipulation of the most effective projects contest selection: to the search of the investment resources accumulation instrument into industrial building.Results. It is stipulated that state investment policy in industrial building mechanism oriented to define rational investment volumes and their branch, reproductive, technological and territorial structure; option of the building branch development priority; increase of the investment projects efficiency realization. The dynamics of the state support in the form of subsidies and budget investments into creation of the industrial building objects is analytically summarized. It is determined that the peculiarity of the modern state support projects of industrial building is transition from budget allocations distribution between branches and regions to selective and partial financing of specific investment projects on competitive basis. Some tactics of state and private partnership attracting private capital without losing strategic state control under systems and objects are defined. As an effective form of the industrial building support projects it is proposed to use a concession model form: projecting - building- financing- ownership - exploitation.Conclusion. The state support projects system of the industrial building provides the realization of all concerned people's economic interests at all stages of creating, realizing, crediting, contracts concluding and objects commissioning. The concession support model allows the state to get a number of advantages solving the problem of budget load reduction by attracting private capital. The state support forms development of industrial building promotes the competitive industrial base forming the prospect of the stable economic growth in Russia. The work has been done in the frameworks of the state order of the Ministry of Education and Science of the Russian Federation No. 2916 «Development of the organizational-economic mechanism of effective development of economic sectors».